Право на інформацію в кримінальному провадженні у контексті міжнародно-правових стандартів - Пчеліна, О. В.; Pchelina, O. V.; Пчеліна Оксана Василівна (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2021. – № 3. - С. 266-271, 2021)
Здійснено аналіз наукових підходів до трактування поняття та значення інституту міжнародноправових стандартів. Визначено сутність права на інформацію та його місце в системі прав і свобод людини. З‘ясовано поняття та зміст права на інформацію в кримінальному провадженні у контексті міжнародно-правових стандартів. Запропоновано право на інформацію в кримінальному провадженні розуміти як передбачену кримінальним процесуальним законодавством України можливість і порядок отримання, використання, поширення, зберігання та захисту інформації, що визначається засадами кримінального провадження та забезпечує вирішення його завдань.

It has been noted that such activities are a sphere of public life, which is inextricably linked with the need and possibility of coercion, which clearly indicates the restriction of certain human rights and freedoms to ensure the effectiveness of pre-trial investigation and trial. The provisions of international legal acts proclaiming and ensuring human rights and fundamental freedoms in criminal proceedings have been analyzed. It has been emphasized that in the specified international legal acts there is no interpretation of the right to information, and also it is not considered as the separate right. The essence of the right to information and its place in the system of human rights and freedoms has been determined. The author‘s understanding of the concept of the right to information in criminal proceedings has been offered, its content has been revealed and its compliance with international standards of human rights and freedoms has been clarified. The right to information in criminal proceedings has been defined as the possibility and procedure for obtaining, using, disseminating, storing and protecting information provided by the criminal procedure legislation of Ukraine, which determines the principles of criminal proceedings and ensures the solution of its tasks. It has been emphasized that the right to information in criminal proceedings in the context of international legal standards is multifaceted in nature, which allows us to consider it in several aspects, namely as: the basis of criminal proceedings; providing information on procedural rights; informing the person about his / her detention, suspicion / accusation of committing a criminal offense; gaining access to information on material evidence; a ban on the disclosure of information obtained during the pre-trial investigation and court proceedings, and its use not to solve the problems of criminal proceedings.

Осуществлен анализ научных подходов к трактовке понятия и значения института международно-правовых стандартов. Определена сущность права на информацию и его место в системе прав и свобод человека. Выяснено понятие и содержание права на информацию в уголовном производстве в контексте международно-правовых стандартов. Предложено право на информацию в уголовном производстве понимать как предусмотренную уголовным процессуальным законодательством Украины возможность и порядок получения, использования, распространения, хранения и защиты информации, что определяется основами уголовного производства и обеспечивает решения его задач.
The right to information in criminal proceedings in the context of international legal standards
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; уголовное производство; criminal proceedings; право на інформацію; право на информацию; right to information; міжнародно-правові стандарти; международно-правовые стандарты; international legal standards; права і свободи людини; права и свободы человека; human rights and freedoms; законодавство; законодательство; legislation